Preparation and application of a potassium ion battery cathode material

CN120423515BActive Publication Date: 2026-10-09JIANGSU ZENIO NEW ENERGY BATTERY TECH CO LTD
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202510581978.X
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2025-05-07
Publication Date
2026-10-09
Estimated Expiration
2045-05-07

AI Technical Summary

Technical Problem

[0005]但这还不能满足市场需求,需要开发出一种结构稳定、工作电位较高、循环稳定性较好的储钾阴极材料

Benefits of technology

[0028] The potassium-ion battery cathode material β-KVOPO4 prepared by this invention has excellent structural stability and high operating voltage, and exhibits good cycle stability. It can be matched with a variety of anode materials to prepare potassium-ion secondary batteries with high energy density, which has profound significance for the application of potassium storage secondary battery cathode materials.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005391553830000101
    Figure BDA0005391553830000101
  • Figure BDA0005391553830000111
    Figure BDA0005391553830000111
Patent Text Reader

Abstract

The application relates to a preparation method of a potassium ion battery cathode material, comprising the following steps: S1: mixing a vanadium source, a phosphorus source and citric acid, drying, and first calcining to obtain a mixture precursor; S2: mixing the mixture precursor obtained in the step S1 and a potassium source, and second calcining, so that the cathode material is obtained. The prepared potassium ion battery cathode material beta-KVOPO4 has excellent structural stability and a relatively high working voltage, exhibits good cycle stability, can be matched with various anode materials to prepare a potassium ion secondary battery with high energy density, and has far-reaching significance in the application of the potassium ion secondary battery cathode material.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of potassium-ion battery technology, and in particular to the preparation and application of a potassium-ion battery cathode material. Background Technology

[0002] In recent years, the rapid development of lithium-ion batteries has led to the massive depletion of lithium resources, resulting in a gradual increase in the cost of lithium batteries and limiting their large-scale application. Potassium, an alkali metal in the same group as lithium, is not only abundant in the Earth's crust but also has a redox potential closer to that of lithium, possessing a high energy density. However, because potassium ions have a larger radius than lithium ions, their insertion and extraction are more difficult. Therefore, finding potassium-containing cathode materials with larger potassium ion migration channels and high performance is a key challenge for the development of potassium-ion batteries.

[0003] Currently, while some transition metal oxides, Prussian blue compounds, and polyanionic cathode materials have exhibited suitable potassium storage performance, their advantages and disadvantages are also quite prominent. For example, layered oxide cathode materials, although theoretically having a high specific capacity and K0.05, have significant limitations. + Two-dimensional diffusion within the layers is relatively fast, but the operating potential of layered oxides is low, and the interaction between interlayer oxygens is strong, at K... + Phase transitions easily occur during insertion / extraction, severely affecting structural stability and resulting in poor electrochemical cycling performance. In contrast to the low operating potentials of layered transition metal oxides, Prussian blue compounds, while exhibiting high operating voltages, are highly unstable in air due to their unique structural defects that attract a large number of water molecules for coordination. Polyanionic materials, on the other hand, have stable framework structures and K... + The volume change during insertion / extraction is small, exhibiting excellent structural stability, as well as high operating potential and cycle stability.

[0004] Polyanionic materials are a class of highly promising cathode materials for potassium-ion batteries. β-KVOPO4, as a type of polyanionic material, has a high operating potential and theoretical specific capacity. Its unique crystal structure enables multi-electron transfer and exhibits good cycle stability.

[0005] However, this is still insufficient to meet market demand. There is a need to develop a potassium storage cathode material with stable structure, high operating potential, and good cycle stability. Summary of the Invention

[0006] The problem the invention aims to solve

[0007] To address the shortcomings of existing technologies, the present invention aims to provide a method for preparing and applying a potassium-ion battery cathode material. This cathode material, β-KVOPO4, exhibits excellent structural stability, a high operating voltage, and good cycle stability.

[0008] Solution for solving the problem

[0009] To achieve this objective, the present invention employs the following technical solution:

[0010] In a first aspect, the present invention provides a method for preparing a potassium-ion battery cathode material, comprising the following steps:

[0011] S1: Mix vanadium source, phosphorus source and citric acid, dry and calcine for the first time to obtain a mixed precursor;

[0012] S2: Mix the precursor obtained in step S1 with the potassium source and calcine it for a second time to obtain the cathode material.

[0013] Preferably, the vanadium source includes at least one selected from vanadium dioxide, vanadium trioxide, vanadium pentoxide, or ammonium metavanadate; and / or,

[0014] The phosphorus source includes at least one of ammonium phosphate, diammonium hydrogen phosphate, or ammonium dihydrogen phosphate; and / or,

[0015] The potassium source includes at least one of potassium dihydrogen phosphate, potassium carbonate, or potassium oxalate.

[0016] Preferably, in step S1, the molar ratio of the vanadium source to the phosphorus source is 1:(1-2), and the amount of citric acid added satisfies the condition that its carbon content accounts for 8wt% to 15wt% of the mass of the cathode material (the product obtained in step S2).

[0017] Preferably, in step S1, the mixing method is magnetic stirring, and the mixing time is 0.5 to 4 hours; and / or,

[0018] The drying method is forced-air drying, with a drying temperature of 80–90℃ and a drying time of 8–24 hours; and / or,

[0019] The temperature of the first calcination is 500-800℃, and the holding time is 6-18 hours.

[0020] Preferably, in step S2, the molar ratio of the mixture precursor to the potassium source is 2:(1-2).

[0021] Preferably, in step S2, the mixing method is ball milling, and the mixing time is 4–12 hours; and / or,

[0022] The second calcination temperature is 600–900℃, and the holding time is 8–16 hours.

[0023] Preferably, step S2 is carried out in an inert gas atmosphere, wherein the inert gas is argon or nitrogen.

[0024] In a second aspect, the present invention provides a cathode material prepared by the cathode material preparation method described in the first aspect.

[0025] Thirdly, the present invention provides a cathode electrode, the cathode electrode comprising the cathode material as described in the second aspect.

[0026] Fourthly, the present invention provides a potassium-ion battery, the potassium-ion battery comprising a cathode electrode as described in the third aspect.

[0027] The present invention has the following beneficial effects:

[0028] The potassium-ion battery cathode material β-KVOPO4 prepared by this invention has excellent structural stability and high operating voltage, and exhibits good cycle stability. It can be matched with a variety of anode materials to prepare potassium-ion secondary batteries with high energy density, which has profound significance for the application of potassium storage secondary battery cathode materials. Detailed Implementation

[0029] To make the technical solution and beneficial effects of the present invention more apparent and understandable, a detailed description is provided below by listing specific embodiments. It should be understood that these embodiments are for illustrative purposes only and are not intended to limit the scope of the invention. Any product identical or similar to the present invention, derived by any person under the guidance of the present invention or by combining the features of the present invention with other prior art, falls within the protection scope of the present invention.

[0030] In the following description, numerous specific details are set forth in order to provide a more thorough understanding of the invention. However, it will be apparent to those skilled in the art that the invention may be practiced without one or more of these details. In other instances, to avoid obscuring the invention, some technical features well-known in the art have not been described; that is, not all features of actual embodiments are described herein, nor are well-known functions and steps described in detail.

[0031] The terminology used herein is for the purpose of describing particular embodiments only and is not intended to limit the invention. When used herein, the singular forms “a,” “an,” and “the” are also intended to include the plural forms unless the context clearly indicates otherwise. It should also be understood that the terms “comprising” and / or “including,” when used in this specification, identify the presence of the stated features, integers, steps, operations, elements, and / or components, but do not exclude the presence or addition of one or more other features, integers, steps, operations, elements, components, and / or groups. When used herein, the term “and / or” includes any and all combinations of the associated listed items.

[0032] To fully understand this invention, detailed steps and structures will be presented in the following description to illustrate the technical solution of this invention. Preferred embodiments of the invention are described in detail below; however, in addition to these detailed descriptions, the invention may have other embodiments.

[0033] Unless otherwise defined, the technical and scientific terms used in this invention have the same meanings as those in the technical and scientific field to which this invention pertains.

[0034] Unless otherwise specified, the techniques or conditions described in the following embodiments are generally performed in accordance with conventional techniques or conditions described in the literature in this field, or in accordance with the product manual and the manufacturer's recommendations. All numerical ranges in the following embodiments include endpoint values.

[0035] [Preparation method of cathode material for potassium-ion batteries]

[0036] In a first aspect, the present invention provides a method for preparing a potassium-ion battery cathode material, comprising the following steps:

[0037] S1: Mix vanadium source, phosphorus source and citric acid, dry and calcine for the first time to obtain a mixed precursor;

[0038] S2: Mix the precursor obtained in step S1 with the potassium source and calcine it for a second time to obtain the cathode material.

[0039] The method for preparing potassium-ion battery cathode materials provided by this invention, through precise control of the mixing, drying, and two calcination processes and conditions, can produce cathode materials with excellent electrochemical performance. In step S1, vanadium source, phosphorus source, and citric acid are mixed. The chelating effect of citric acid ensures uniform dispersion of the vanadium and phosphorus sources, forming a stable mixed system. Subsequent drying and the first calcination process promote the breaking and recombination of chemical bonds in the raw materials, forming a mixed precursor with a specific structure, providing a good basic structure for subsequent potassium ion insertion and extraction. In step S2, the mixed precursor obtained in step S1 is mixed with the potassium source. This process allows the potassium source to contact the precursor uniformly, providing more active sites for potassium ion insertion. The subsequent second calcination is carried out at a specific temperature and atmosphere. This step not only promotes the chemical reaction between the potassium source and the precursor to form the final cathode material, but also further optimizes the crystal structure of the material through high-temperature calcination, improving the crystallinity and stability of the material. This results in a cathode material with higher operating voltage and better cycle stability, which can meet the requirements of potassium-ion batteries in terms of high energy density and long cycle life.

[0040] In some embodiments, the vanadium source includes at least one of vanadium dioxide, vanadium trioxide, vanadium pentoxide, or ammonium metavanadate.

[0041] In some embodiments, the vanadium source is ammonium metavanadate.

[0042] In some embodiments, the phosphorus source includes at least one of ammonium phosphate, diammonium hydrogen phosphate, or ammonium dihydrogen phosphate.

[0043] In some embodiments, the phosphorus source is ammonium dihydrogen phosphate.

[0044] In some embodiments, the potassium source includes at least one of potassium dihydrogen phosphate, potassium carbonate, or potassium oxalate.

[0045] In some embodiments, the potassium source is potassium carbonate.

[0046] In some embodiments, in step S1, the molar ratio of the vanadium source to the phosphorus source is 1:(1-2), for example, 1:1.0, 1:1.1, 1:1.2, 1:1.3, 1:1.4, 1:1.5, 1:1.6, 1:1.7, 1:1.8, 1:1.9, or 1:2.0, but not limited to the listed values; other unlisted values ​​within the range are also applicable. The amount of citric acid added satisfies the condition that its carbon content accounts for 8wt% to 15wt% of the mass of the cathode material (the product obtained in step S2), for example, 8wt%, 9wt%, 10wt%, 11wt%, 12wt%, 13wt%, 14wt%, or 15wt%, but not limited to the listed values; other unlisted values ​​within the range are also applicable. This invention achieves optimal coating effect by controlling the amount of citric acid added. If too much citric acid is added, the carbon coating layer will be too thick, which is not conducive to the diffusion of potassium ions. Conversely, if too little citric acid is added, it will lead to a decrease in battery rate performance.

[0047] In some embodiments, in step S1, the molar ratio of the vanadium source to the phosphorus source is 1:(1-2), and the amount of citric acid added satisfies the condition that its carbon content accounts for 8wt% to 12wt% of the mass of the cathode material (the product obtained in step S2).

[0048] In some embodiments, in step S1, the mixing method is magnetic stirring, and the mixing time is 0.5 to 4 hours, for example, 0.5 hours, 1.0 hour, 1.5 hours, 2.0 hours, 2.5 hours, 3.0 hours, 3.5 hours, or 4.0 hours, but not limited to the listed values; other unlisted values ​​within the range are also applicable. This invention achieves uniform mixing and optimal particle size by controlling the stirring time. If the stirring time is too long, the particle size will be too small, resulting in poor high-temperature performance of the battery. Conversely, if the stirring time is too short, insufficient mixing will occur.

[0049] In some embodiments, in step S1, the drying method is forced-air drying, and the drying temperature is 80-90℃, such as 80℃, 81℃, 82℃, 83℃, 84℃, 85℃, 86℃, 87℃, 88℃, 89℃, or 90℃, but not limited to the listed values; other unlisted values ​​within the range are also applicable. The drying time is 8-24 hours, such as 8 hours, 9 hours, 10 hours, 11 hours, 12 hours, 13 hours, 14 hours, 15 hours, 16 hours, 17 hours, 18 hours, 19 hours, 20 hours, 21 hours, 22 hours, 23 hours, or 24 hours, but not limited to the listed values; other unlisted values ​​within the range are also applicable. This invention maintains the structural stability of the material while ensuring the precursor of the mixture is fully dried by controlling the drying temperature and time parameters. If the drying temperature is too low or the drying time is too short, the water content of the mixed precursor will be too high, causing problems such as electrolyte decomposition leading to HF corrosion of the electrodes and SEI film structural defects, ultimately resulting in a sharp capacity decay during battery cycling. Conversely, if the drying temperature is too high or the drying time is too long, it can damage the structure of the electrode active material.

[0050] In some embodiments, in step S1, the temperature of the first calcination is 500–800°C, for example, 500°C, 550°C, 600°C, 650°C, 700°C, 750°C, or 800°C, but not limited to the listed values; other unlisted values ​​within the range are also applicable. The holding time is 6–18 hours, for example, 6 hours, 7 hours, 8 hours, 9 hours, 10 hours, 11 hours, 12 hours, 13 hours, 14 hours, 15 hours, 16 hours, 17 hours, or 18 hours, but not limited to the listed values; other unlisted values ​​within the range are also applicable. This invention improves calcination efficiency and obtains a mixture precursor by controlling the calcination temperature and / or holding time.

[0051] In some embodiments, in step S1, the temperature of the first calcination is 600-800°C, and the holding time is 10-18 hours.

[0052] In some embodiments, in step S2, the molar ratio of the mixture precursor to the potassium source is 2:(1-2), for example 2:1.0, 2:1.1, 2:1.2, 2:1.3, 2:1.4, 2:1.5, 2:1.6, 2:1.7, 2:1.8, 2:1.9 or 2:2.0, but is not limited to the listed values. Other unlisted values ​​within the range are also applicable.

[0053] In some embodiments, in step S2, the mixing method is ball milling, and the mixing time is 4 to 12 hours, for example, 4 hours, 5 hours, 6 hours, 7 hours, 8 hours, 9 hours, 10 hours, 11 hours, or 12 hours, but not limited to the listed values; other unlisted values ​​within the range are also applicable. This invention ensures uniform mixing of the precursor and potassium source by controlling the ball milling time. If the ball milling time is too short, the mixing will be insufficient, which may affect the performance of the cathode material obtained after the second calcination step.

[0054] In some embodiments, in step S2, the mixing method is ball milling, and the mixing time is 4 to 6 hours.

[0055] In some embodiments, the temperature of the second calcination is 600–900°C, for example, 600°C, 650°C, 700°C, 750°C, 800°C, 850°C, or 900°C, but not limited to the listed values; other unlisted values ​​within the range are also applicable. The holding time is 8–16 hours, for example, 8 hours, 9 hours, 10 hours, 11 hours, 12 hours, 13 hours, 14 hours, 15 hours, or 16 hours, but not limited to the listed values; other unlisted values ​​within the range are also applicable. This invention improves calcination efficiency and obtains cathode materials with excellent performance by controlling the calcination temperature and / or holding time.

[0056] In some embodiments, step S2 includes a second drying process before the second calcination and after the mixing.

[0057] In some embodiments, the second drying method is forced air drying, and the second drying temperature is 80-90°C, such as 80°C, 81°C, 82°C, 83°C, 84°C, 85°C, 86°C, 87°C, 88°C, 89°C, or 90°C, but not limited to the listed values; other unlisted values ​​within the range are also applicable. The second drying time is 8-24 hours, such as 8 hours, 9 hours, 10 hours, 11 hours, 12 hours, 13 hours, 14 hours, 15 hours, 16 hours, 17 hours, 18 hours, 19 hours, 20 hours, 21 hours, 22 hours, 23 hours, or 24 hours, but not limited to the listed values; other unlisted values ​​within the range are also applicable.

[0058] In some embodiments, step S2 is performed in an inert gas atmosphere, wherein the inert gas is argon or nitrogen.

[0059] [Cathode Material]

[0060] In a second aspect, the present invention provides a cathode material prepared by the cathode material preparation method described in the first aspect.

[0061] The cathode material described in this invention is β-KVOPO4.

[0062] It should be understood that, since the cathode material provided by the present invention is prepared by the cathode material preparation method provided by the first aspect of the present invention, the beneficial effects of preparing the cathode material in any of the above embodiments are applicable to the cathode material.

[0063] [Cathode electrode]

[0064] Thirdly, the present invention provides a cathode electrode, the cathode electrode comprising the cathode material as described in the second aspect.

[0065] The cathode electrode in this invention may further include a conductive agent and a binder. There are no particular limitations on the types of conductive agents and binders in the cathode electrode, as long as they achieve the purpose of this invention. For example, the binder may include, but is not limited to, polyvinyl alcohol, hydroxypropyl cellulose, diacetyl cellulose, polyvinyl chloride, carboxylated polyvinyl chloride, polyvinyl fluoride, polymers containing ethylene oxide, polyvinylpyrrolidone, polyurethane, polytetrafluoroethylene, polyvinylidene 1,1-difluoroethylene, polyethylene, polypropylene, styrene-butadiene rubber, acrylated styrene-butadiene rubber, epoxy resin, or nylon, etc. For example, the conductive agent may include, but is not limited to, conductive carbon black, acetylene black, Ketjen black, carbon fiber, or any combination thereof.

[0066] The present invention does not impose any particular restrictions on the preparation method of the cathode electrode. Any preparation method known in the art can be used, as long as it can achieve the purpose of the present invention.

[0067] It should be understood that since the cathode electrode provided by the present invention includes the cathode material described in the second aspect of the present invention, the beneficial effects of preparing the cathode material described in any of the above embodiments are applicable to the cathode electrode.

[0068] Potassium-ion batteries

[0069] Fourthly, the present invention provides a potassium-ion battery, the potassium-ion battery comprising a cathode electrode as described in the third aspect.

[0070] The potassium-ion battery in this invention includes a potassium-ion secondary battery.

[0071] The battery structure in this invention may also include, but is not limited to, button cells, pouch cells, cylindrical cells, etc.

[0072] The potassium-ion battery of this invention may further include an anode electrode, a cathode electrode, a separator, and an electrolyte. There are no particular limitations on the anode electrode, separator, and electrolyte in the potassium-ion battery; those skilled in the art can choose according to actual needs, as long as the purpose of this invention can be achieved. For example, the separator may be one of the following: polypropylene separator (PP), polyethylene separator (PE), polypropylene / polyethylene double-layer composite membrane (PP / PE), polypropylene / polyethylene / polypropylene triple-layer composite membrane (PP / PE / PP), polyimide electrospun separator (PI), cellulose nonwoven separator, polyethylene terephthalate nonwoven separator (PET), and separator with a ceramic coating.

[0073] The reagents, instruments, and materials used in this invention can all be obtained through commercial channels.

[0074] The method of the present invention will be described below through specific embodiments. It should be understood that these embodiments are used to illustrate the basic principles, main features and advantages of the present invention, and the present invention is not limited to the scope of the following embodiments. The implementation conditions used in the embodiments can be further adjusted according to specific requirements, and the implementation conditions not specified are usually the conditions in conventional experiments.

[0075] To enable those skilled in the art to better understand the technical solution of the present invention, the present invention will be further described below through specific embodiments 1-3 and comparative examples 1-2.

[0076] Example 1

[0077] 1. Synthesis of β-VOPO4 precursor: A certain amount of ammonium metavanadate and ammonium dihydrogen phosphate were weighed in a molar ratio of 1:1, and citric acid with a carbon content of 10 wt% of the target product β-KVOPO4 was weighed. The mixture was added to 100 mL of deionized water and stirred in a constant temperature water bath at 80 °C for 3 hours until the citric acid and other raw materials were completely dissolved. The obtained solution was dried in a forced-air drying oven at 85 °C for 24 hours. The dried material was then calcined in a muffle furnace at 650 °C for 14 hours to obtain the β-VOPO4 precursor.

[0078] 2. Synthesis of β-KVOPO4 material: A certain amount of β-VOPO4 precursor and potassium carbonate were weighed according to a molar ratio of 2:1, mixed evenly, transferred to an agate ball mill jar, and 20 mL of deionized water was added. The mixture was ball-milled for 6 hours using a high-speed planetary ball mill. The milled material was then placed in an 85°C drying oven and dried for 24 hours. A suitable amount of the dried sample was then calcined in a high-temperature tube furnace at 600°C under an argon atmosphere for 10 hours. After cooling, the material was ground to obtain β-KVOPO4 material.

[0079] 3. Preparation of coin cell: Using NMP (N-methylpyrrolidone) as solvent, the β-KVOPO4 material prepared in this example was thoroughly ground with acetylene black and PVDF (polyvinylidene fluoride) at a mass ratio of 80:10:10. The resulting slurry was evenly coated onto aluminum foil and dried in a vacuum drying oven at 100°C for 12 hours to obtain the cathode sheet. A potassium-ion battery electrolyte was prepared using a solution of 0.8 mol / L KPF6 ethylene carbonate and propylene carbonate (mass ratio 3:7) and 1 wt% fluoroethylene carbonate. Glass fiber and potassium metal sheets were used as the potassium-ion battery separator and anode, respectively, to assemble a CR2032 type coin cell. Battery assembly was carried out in an argon-filled glove box, with water and oxygen concentrations both less than 0.1 ppm.

[0080] 4. Electrochemical performance testing: The CR2032 coin cell prepared in Example 1 was tested using a Blue Electric CT2001A battery testing system at 2.0–4.0 V (vs. K). + Within the voltage range of / K), constant current charge-discharge cycle tests were conducted at room temperature (25℃) with current densities of 20mA / g, 50mA / g, 100mA / g, and 200mA / g, respectively.

[0081] The test results are shown in Table 1. At a current density of 200 mA / g, the capacity retention rate after 200 cycles at room temperature (25℃) is 88.6%, which shows good cycle stability.

[0082] Table 1 Electrochemical performance data of button half-cell in Example 1

[0083] 20 89.2 92.6 50 88.6 91.8 100 87.6 90.8 200 86.9 88.6

[0084] Example 2

[0085] 1. Synthesis of β-VOPO4 precursor: A certain amount of ammonium metavanadate and ammonium dihydrogen phosphate were weighed in a molar ratio of 1:1, and citric acid with a carbon content of 15 wt% of the target product β-KVOPO4 was weighed. The mixture was added to 150 mL of deionized water and stirred in a constant temperature water bath at 80 °C for 3 hours until the citric acid and other raw materials were completely dissolved. The obtained solution was dried in a forced-air drying oven at 85 °C for 24 hours. The dried material was then calcined in a muffle furnace at 650 °C for 14 hours to obtain the β-VOPO4 precursor.

[0086] 2. Synthesis of β-KVOPO4 material: A certain amount of β-VOPO4 precursor and potassium carbonate were weighed according to a molar ratio of 2:1, mixed evenly, transferred to an agate ball mill jar, and 20 mL of deionized water was added. The mixture was ball-milled for 6 hours using a high-speed planetary ball mill. The milled material was then placed in an 85°C drying oven and dried for 24 hours. A suitable amount of the dried sample was then calcined in a high-temperature tube furnace at 600°C under an argon atmosphere for 10 hours. After cooling, the material was ground to obtain β-KVOPO4 material.

[0087] 3. Preparation of coin cell: Using NMP (N-methylpyrrolidone) as solvent, the β-KVOPO4 material prepared in this example was thoroughly ground with acetylene black and PVDF (polyvinylidene fluoride) at a mass ratio of 80:10:10. The resulting slurry was evenly coated onto aluminum foil and dried in a vacuum drying oven at 100°C for 12 hours to obtain the cathode sheet. A potassium-ion battery electrolyte was prepared using a solution of 0.8 mol / L KPF6 ethylene carbonate and propylene carbonate (mass ratio 3:7) and 1 wt% fluoroethylene carbonate. Glass fiber and potassium metal sheets were used as the potassium-ion battery separator and anode, respectively, to assemble a CR2032 type coin cell. Battery assembly was carried out in an argon-filled glove box, with water and oxygen concentrations both less than 0.1 ppm.

[0088] 4. Electrochemical performance testing: The CR2032 coin cell prepared in Example 2 above was tested using a Blue Electric CT2001A battery testing system at 2.0–4.0 V (vs. K). + Within the voltage range of / K), constant current charge-discharge cycle tests were conducted at room temperature (25℃) with current densities of 20mA / g, 50mA / g, 100mA / g, and 200mA / g, respectively.

[0089] The test results are shown in Table 2. At a current density of 200 mA / g, the capacity retention rate after 200 cycles at room temperature (25℃) is 87.8%, which shows good cycle stability.

[0090] Table 2 Electrochemical performance data of button half-cells in Example 2

[0091] 20 88.5 91.2 50 88.1 90.5 100 87.2 90.1 200 86.8 87.8

[0092] Example 3

[0093] 1. Synthesis of β-VOPO4 precursor: A certain amount of ammonium metavanadate and ammonium dihydrogen phosphate were weighed in a molar ratio of 1:1, and citric acid with a carbon content of 10 wt% of the target product β-KVOPO4 was weighed. The mixture was added to 100 mL of deionized water and stirred in a constant temperature water bath at 80 °C for 3 hours until the citric acid and other raw materials were completely dissolved. The obtained solution was dried in a forced-air drying oven at 85 °C for 24 hours. The dried material was then calcined in a muffle furnace at 700 °C for 12 hours to obtain the β-VOPO4 precursor.

[0094] 2. Synthesis of β-KVOPO4 material: A certain amount of β-VOPO4 precursor and potassium carbonate were weighed according to a molar ratio of 2:1, mixed evenly, transferred to an agate ball mill jar, and 20 mL of deionized water was added. The mixture was ball-milled for 6 hours using a high-speed planetary ball mill. The milled material was then placed in an 85°C drying oven and dried for 24 hours. A suitable amount of the dried sample was then calcined in a high-temperature tube furnace at 600°C under an argon atmosphere for 10 hours. After cooling, the material was ground to obtain β-KVOPO4 material.

[0095] 3. Preparation of coin cell: Using NMP (N-methylpyrrolidone) as solvent, the β-KVOPO4 material prepared in this example was thoroughly ground with acetylene black and PVDF (polyvinylidene fluoride) at a mass ratio of 80:10:10. The resulting slurry was evenly coated onto aluminum foil and dried in a vacuum drying oven at 100°C for 12 hours to obtain the cathode sheet. A potassium-ion battery electrolyte was prepared using a solution of 0.8 mol / L KPF6 ethylene carbonate and propylene carbonate (mass ratio 3:7) and 1 wt% fluoroethylene carbonate. Glass fiber and potassium metal sheets were used as the potassium-ion battery separator and anode, respectively, to assemble a CR2032 type coin cell. Battery assembly was carried out in an argon-filled glove box, with water and oxygen concentrations both less than 0.1 ppm.

[0096] 4. Electrochemical performance testing: The CR2032 coin cell prepared in Example 3 above was tested using a Blue Electric CT2001A battery testing system at 2.0–4.0 V (vs. K). + Within the voltage range of / K), constant current charge-discharge cycle tests were conducted at room temperature (25℃) with current densities of 20mA / g, 50mA / g, 100mA / g, and 200mA / g, respectively.

[0097] The test results are shown in Table 3. At a current density of 200 mA / g, the capacity retention rate after 200 cycles at room temperature (25℃) is 87.3%, which shows good cycle stability.

[0098] Table 3 Electrochemical performance data of button half-cell in Example 3

[0099] 20 88.9 91.6 50 88.4 90.8 100 87.4 89.9 200 86.5 87.6

[0100] Comparative Example 1

[0101] 1. Synthesis of β-KVOPO4 material: A certain amount of ammonium metavanadate, ammonium dihydrogen phosphate and potassium carbonate were weighed according to a molar ratio of 2:2:1 and added to 100 mL of deionized water. The mixture was stirred in a constant temperature water bath at 80 °C for 3 hours. The resulting solution was then dried in a forced-air drying oven at 85 °C for 24 hours. The dried material was then placed in a tube furnace and kept at 800 °C under an argon atmosphere for 8 hours. After cooling, the material was ground to obtain β-KVOPO4 material.

[0102] 2. Preparation of coin cell: Using NMP (N-methylpyrrolidone) as solvent, the β-KVOPO4 material prepared in this example was thoroughly ground with acetylene black and PVDF (polyvinylidene fluoride) at a mass ratio of 80:10:10. The resulting slurry was evenly coated onto aluminum foil and dried in a vacuum drying oven at 100°C for 12 hours to obtain the cathode sheet. A potassium-ion battery electrolyte was prepared using a solution of 0.8 mol / L KPF6 ethylene carbonate and propylene carbonate (mass ratio 3:7) and 1 wt% fluoroethylene carbonate. Glass fiber and potassium metal sheets were used as the potassium-ion battery separator and anode, respectively, to assemble a CR2032 type coin cell. Battery assembly was carried out in an argon-filled glove box, with water and oxygen concentrations both less than 0.1 ppm.

[0103] 3. Electrochemical performance testing: The CR2032 coin cell prepared in Comparative Example 1 was tested using the Blue Electric CT2001A battery testing system at 2.0–4.0 V (vs. K). + Within the voltage range of / K), constant current charge-discharge cycle tests were conducted at room temperature (25℃) with current densities of 20mA / g, 50mA / g, 100mA / g, and 200mA / g, respectively.

[0104] The test results are shown in Table 4. At a current density of 200 mA / g, the capacity retention rate after 200 cycles at room temperature (25℃) is 87.0%.

[0105] Table 4 Electrochemical performance data of the button half-cell in Comparative Example 1

[0106] 20 87.2 90.1 50 86.5 89.2 100 85.2 88.1 200 83.5 87.0

[0107] Comparative Example 2

[0108] 1. Synthesis of β-KVOPO4 material: A certain amount of ammonium metavanadate, ammonium dihydrogen phosphate and potassium carbonate were weighed according to a molar ratio of 2:2:1 and added to 100 mL of deionized water. The mixture was stirred in a constant temperature water bath at 80 °C for 3 hours. The resulting solution was then dried in a forced-air drying oven at 85 °C for 24 hours. The dried material was then placed in a tube furnace at 600 °C under an argon atmosphere and kept at that temperature for 10 hours. After cooling, the material was ground to obtain β-KVOPO4 material.

[0109] 2. Preparation of coin cell: Using NMP (N-methylpyrrolidone) as solvent, the β-KVOPO4 material prepared in this example was thoroughly ground with acetylene black and PVDF (polyvinylidene fluoride) at a mass ratio of 80:10:10. The resulting slurry was evenly coated onto aluminum foil and dried in a vacuum drying oven at 100°C for 12 hours to obtain the cathode sheet. A potassium-ion battery electrolyte was prepared using a solution of 0.8 mol / L KPF6 ethylene carbonate and propylene carbonate (mass ratio 3:7) and 1 wt% fluoroethylene carbonate. Glass fiber and potassium metal sheets were used as the potassium-ion battery separator and anode, respectively, to assemble a CR2032 type coin cell. Battery assembly was carried out in an argon-filled glove box, with water and oxygen concentrations both less than 0.1 ppm.

[0110] 3. Electrochemical performance testing: The CR2032 coin cell prepared in Comparative Example 2 was tested using the Blue Electric CT2001A battery testing system at 2.0–4.0 V (vs. K). + Within the voltage range of / K), constant current charge-discharge cycle tests were conducted at room temperature (25℃) with current densities of 20mA / g, 50mA / g, 100mA / g, and 200mA / g, respectively.

[0111] The test results are shown in Table 5. At a current density of 200 mA / g, the capacity retention rate after 200 cycles at room temperature (25℃) is 87.5%.

[0112] Table 5 Electrochemical performance data of button half-cells in Comparative Example 2

[0113]

[0114]

[0115] Electrochemical performance comparison between Examples 1-3 and Comparative Examples 1-2:

[0116] In terms of synthesis process, Examples 1-3 adopted a two-step method: firstly synthesizing the β-VOPO4 precursor (optimized by calcination and ball milling process), and then introducing a potassium source by combining secondary calcination. Compared with Comparative Examples 1-2 (one-step method), the two-step method of Examples 1-3 can effectively control the crystal growth path and endow the material with a more uniform particle distribution and a stable layered structure.

[0117] In terms of performance, Examples 1-3, after 200 cycles at room temperature (25°C) with a current density of 200 mA / g, exhibited a capacity retention of 87.6%–88.6%, significantly better than the 87.0%–87.5% of Comparative Examples 1-2. This indicates that the β-KVOPO4 material prepared by the two-step method demonstrates higher stability during long-term cycling. Examples 1-3, at a current density of 20 mA / g, showed an initial coulombic efficiency of 88.5%–89.2%, slightly higher than the 87.2%–88.1% of Comparative Examples 1-2. This result indicates that the material prepared by the two-step method experiences less energy loss during the initial charge-discharge cycle. Examples 1-3 consistently demonstrated high capacity retention at different current densities (50 mA / g, 100 mA / g, 200 mA / g), showcasing the material's stable performance under different current conditions. In contrast, Comparative Examples 1-2 exhibited slightly lower capacity retention at different current densities.

[0118] In summary, Examples 1-3 achieved a comprehensive improvement in the microstructure and electrochemical performance of the materials, and prepared potassium-ion battery cathode materials with superior electrochemical performance.

[0119] It should be understood that the above embodiments are exemplary and are not intended to encompass all possible implementations included in the claims. Various modifications and changes can be made to the above embodiments without departing from the scope of this disclosure. Similarly, the various technical features of the above embodiments can be arbitrarily combined to form other embodiments of the present invention that may not be explicitly described. Therefore, the above embodiments only illustrate several implementations of the present invention and do not limit the scope of protection of this patent.

Claims

1. A method for preparing a potassium-ion battery cathode material, characterized in that, Includes the following steps: S1: Mix vanadium source, phosphorus source and citric acid, dry and calcine for the first time to obtain a mixed precursor; S2: Mix the precursor mixture obtained in step S1 with the potassium source and calcine it for the second time to obtain the cathode material; The amount of citric acid added meets the condition that its carbon content accounts for 8 wt% to 15 wt% of the cathode material. The potassium source is potassium carbonate.

2. The method for preparing the cathode material according to claim 1, characterized in that, The vanadium source includes at least one of vanadium dioxide, vanadium trioxide, vanadium pentoxide, or ammonium metavanadate; and / or, The phosphorus source includes at least one of ammonium phosphate, diammonium hydrogen phosphate, or ammonium dihydrogen phosphate.

3. The method for preparing the cathode material according to claim 1, characterized in that, In step S1, the molar ratio of the vanadium source to the phosphorus source is 1:(1-2).

4. The method for preparing the cathode material according to claim 1, characterized in that, In step S1, the mixing method is magnetic stirring, and the mixing time is 0.5 to 4 hours; and / or, The drying method is forced-air drying, with a drying temperature of 80–90℃ and a drying time of 8–24 hours; and / or, The temperature of the first calcination is 500-800℃, and the holding time is 6-18 hours.

5. The method for preparing the cathode material according to claim 1, characterized in that, In step S2, the molar ratio of the mixture precursor to the potassium source is 2:(1-2).

6. The method for preparing the cathode material according to claim 1, characterized in that, In step S2, the mixing method is ball milling, and the mixing time is 4–12 hours; and / or, The second calcination temperature is 600–900℃, and the holding time is 8–16 hours.

7. The method for preparing the cathode material according to claim 1, characterized in that, Step S2 is carried out in an inert gas atmosphere, wherein the inert gas is argon or nitrogen.

8. A cathode material, characterized in that, The cathode material is prepared using the method described in any one of claims 1 to 7.

9. A cathode electrode, characterized in that, The cathode electrode comprises the cathode material as described in claim 8.

10. A potassium-ion battery, characterized in that, The potassium-ion battery includes the cathode electrode as described in claim 9.

Citation Information

Patent Citations

  • Electrode material for rechargeable metal-ion batteries and method of producing same

    WO2017058061A1